2021
DOI: 10.1016/j.arthro.2021.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Tranexamic Acid Is Beneficial in the Very Early Postoperative Period in Anterior Cruciate Ligament Reconstruction Patients

Abstract: Tranexamic acid (TXA) has been administrated in many orthopaedic surgical procedures to decrease perioperative and postsurgical bleeding. Relatively scant literature exists regarding the effect of TXA in patients after anterior cruciate ligament reconstruction. Currently, most evidence shows that within about 1 month after anterior cruciate ligament reconstruction, TXA can effectively reduce postoperative joint swelling and pain, as well as the aspiration rate. However, there are still controversies regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This finding was supported by several randomized controlled trials (RCTs) demonstrating that IV TXA administration protocols could reduce postoperative pain and enhance functional outcomes after ACL reconstruction and meniscectomy 7,28 . A single intra-articular injection of 1 g (100 mg/mL) of TXA was found to considerably reduce postoperative hemarthrosis and pain in the early postoperative period after ACL reconstructions with hamstring grafts 6,10 . However, a double-blinded RCTof patients who underwent ACL reconstruction found no significant differences in perioperative blood loss, postoperative hemarthrosis, or pain levels between those treated with and without IV TXA 29 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This finding was supported by several randomized controlled trials (RCTs) demonstrating that IV TXA administration protocols could reduce postoperative pain and enhance functional outcomes after ACL reconstruction and meniscectomy 7,28 . A single intra-articular injection of 1 g (100 mg/mL) of TXA was found to considerably reduce postoperative hemarthrosis and pain in the early postoperative period after ACL reconstructions with hamstring grafts 6,10 . However, a double-blinded RCTof patients who underwent ACL reconstruction found no significant differences in perioperative blood loss, postoperative hemarthrosis, or pain levels between those treated with and without IV TXA 29 .…”
Section: Discussionmentioning
confidence: 98%
“…In addition to inconsistent clinical results, safety concerns have been raised regarding the use of TXA in the joint space 10,13,30 . While previous studies have demonstrated the cytotoxicity of TXA, there is a lack of in vivo studies examining the impact of topical use of TXA on intra-articular tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations